Therapeutic Management of Cattle Suffering From Anaplasmosis - Ravina; Singh, Yudhbir; Jhambh, Ricky; Charaya, Gaurav (International Journal of Livestock Research, 2025)
The present clinical study highlights the therapeutic management of anaplasmosis in cattle. A total of 21 cattle presented to Veterinary Clinical Complex, LUVAS, Hisar, suspected to be suffering from tick-borne disease based on clinical signs, were considered for the present study. Blood samples were collected in EDTA vials and serum collecting vials for microscopic examination, PCR assay, and evaluation of haemato-biochemical alterations. Blood smear examination revealed nine samples (42.85%) positive for anaplasmosis, and among them, three were found to be of concurrent infection with theileria. A therapeutic regimen using long acting oxytetracycline along with supportive therapy was given to seven clinical cases and hematobiochemical parameters were tested on day 0 and day 5 of post-treatment by day 5th of treatment. Treated cases included six cases of single infection and one case of concurrent infection with Theileria annulata having low parasetemia, and the remaining two were treated with Buparvaquone in addition to oxytetracycline, hence not considered in the study. On day 5th, clinical remission of signs was observed in all the animals with the start of feed intake, and values of all hematobiochemical parameters either returned to normal or approached normal levels.